2017
DOI: 10.9738/intsurg-d-16-00249.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Postoperative Percent Change of Parathormone Level From Baseline Value on the Rate of Hypocalcemia After Total Thyroidectomy

Abstract: Background: To investigate the impact of the percent change of postoperative parathormone (PoPTH) level from baseline value (∆PTH) on the rate of hypocalcemia after total thyroidectomy. Methods: Assays of serum PTH and calcium (Ca) were performed preoperatively and at 24 hours postoperatively in 222 consecutive patients who underwent total thyroidectomy. Postoperative hypocalcemia was defined as serum calcium level corrected for albumin concentration (cCa) <8.5mg/dl. Patients with postoperative hypocalcemia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…In some studies to predict hypocalcemia after bilateral total thyroidectomy, some authors have found success with a single parathormone measurement [11]. As in our study, studies examining the difference between preoperative and postoperative parathormone levels also report successful results [13,14]. In a study by Noordzij et al, the percentage of PTH decline in the postoperative 6 th hour was successful in predicting postoperative hypocalcemia with a cut-off value of %65 [15].…”
Section: Discussionsupporting
confidence: 71%
“…In some studies to predict hypocalcemia after bilateral total thyroidectomy, some authors have found success with a single parathormone measurement [11]. As in our study, studies examining the difference between preoperative and postoperative parathormone levels also report successful results [13,14]. In a study by Noordzij et al, the percentage of PTH decline in the postoperative 6 th hour was successful in predicting postoperative hypocalcemia with a cut-off value of %65 [15].…”
Section: Discussionsupporting
confidence: 71%
“…They suggested that analysis of serum Ca concentrations at 24 hours postoperatively might help to achieve a more precise prediction of patients who bear a high risk for developing hypocalcemic symptoms. [29] Sitges-Serra et al reported in a multicentric prospective study that in 91 (63%) of 145 patients with parathyroid failure (PTH <15 pg/mL at postoperative 4th hour and Ca <8 mg/dL at 24 th hour), hypocalcemia improved in 1 month, and they observed protracted hypoparathyroidism in 54 (37%) patients. They stated that 32 (22%) of these patients recovered in a year, 22 (15%) developed permanent hypoparathyroidism within 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…L. Shifrin, 2021). Sormaz et al, (2021) reported that patients with normal calcium values and PTH values above 28.0 pg/ml six hours after the operation had a very low risk of developing hypocalcemia (Sormaz et al, 2021).…”
Section: Hyperparathyroidismmentioning
confidence: 99%